Studies on multiply exposed but persistently HIV-1 seronegative sex workers from KwaZulu/Natal, South Africa - Malaza, Abraham Lucky (Division of Medical Microbiology, 2017)
The overall aim of this study was to determine whether host genetic factors are associated with resistance to HIV-1 infection in a group of highly exposed persistently seronegative sex workers from KwaZulu/Natal, South Africa. A cohort of 17 African highly exposed but persistently seronegative (HEPS) commercial sex workers (CSW) were identified who had been in sex work for more than four years (range between 4-26 years). The women had been followed monthly for at least four years as part of HIV-1 prevention programmes (Ramjee, et al., 1998). The overall aim of this study was to identify the frequency of polymorphisms and mutations in chemokine genes, chemokine receptors and chemokine receptor promoter region which ma y be associated with HIV-1 resistance and prolonged disease progression. Secondly, to determine if the chemokine receptors on CD4 T-cells are sufficiently expressed and functional to enable infection. This information will shed light on correlates of immunity as influenced by these polymorphisms and this knowledge will help in the bigger objective of determining factors influencing disease progression as well as the development of an effective HIV-1 vaccine in South Africa.